Motivated beliefs, social preferences, and limited liability in financial decision-making - Steffen Ahrens; Ciril Bosch-Rosa (Freie Universität Berlin, School of Business & Economics, 2022)
Using a new experimental design, we compare how subjects form beliefs in an investor-client setup under varying degrees of liability. Our results reflect the importance of social preferences when making investment decisions for others. We show that when investors have no liability, those with stronger social preferences are more optimistic about the probability that their investment results in a gain. In other words, we find that social preferences appear to be correlated with motivated beliefs. This finding suggests the existence of cognitive biases in financial decision-making and supports the recent literature on the formation of motivated beliefs under limited liability (Barberis, 2015; Bénabou and Tirole, 2016).
urn:nbn:de:kobv:188-refubium-36622-5
Keywords: C91; D84; G11; G41; 330; Moral Hazard; Experiment; Motivated Beliefs; Social Preferences